2013
DOI: 10.3892/or.2013.2852
|View full text |Cite
|
Sign up to set email alerts
|

Diethylstilbestrol for the treatment of patients with castration-resistant prostate cancer: Retrospective analysis of a single institution experience

Abstract: Abstract. The aim of the present retrospective study was to evaluate the efficacy and safety of diethylstilbestrol (DES) as treatment for patients with castration-resistant prostate cancer (CRPC) and to identify predicting factors of response to DES. Patients treated with DES during the castration-resistant phase following the failure of prior treatment with LH-RH analogs during the castration-sensitive phase were retrieved from a prostate cancer database of our institution. Patients were treated with a daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…The addition of systemic therapy appears to be necessary to address the issue of distant micrometastases, e.g. endocrine, cytotoxic or immune therapy (21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of systemic therapy appears to be necessary to address the issue of distant micrometastases, e.g. endocrine, cytotoxic or immune therapy (21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…However, human exposure to this chemical still occurs in clinics. It is now still used in hormone replacement therapy for women, and is also accepted as an efficient therapy for prostate (Grenader et al, 2014) and breast cancers (Peethambaram et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, human exposure to this chemical still occurs in clinics. It is now still used in hormone replacement therapy for women, and is also accepted as an efficient therapy for prostate (Grenader et al, 2014) and breast cancers (Peethambaram et al, 1999).Our previous studies demonstrated that DES acts as a good substrate to multiple UDP-glucuronosyltransferases (UGT), including UGT1A1, 1A3, 1A8 and 2B7, with high affinity (Zhu et al, 2012). It appeared that DES may possibly inhibit many UGT isoforms.…”
mentioning
confidence: 98%
“…Other sex steroid receptors, including the oestrogen receptors (ERs; including ESR1 /ERα and ESR2 /ERβ), are also expressed by prostate cancer cells. Therapies targeting ERs have been shown to be active in advanced prostate cancer . While it is not yet known whether ER mutants and splice variants contribute to the progression of prostate cancer, ESR1 missense substitution mutations affect the function of the transcribed ERα ligand‐binding domain, disrupting the normal hormone signalling pathway .…”
Section: Introductionmentioning
confidence: 99%